Representation of Women in Paris Paloma’s Songs: A Gynocritical Literary Analysis - Siti Maemunah; Irma Rahmawati (Indo Publishing, 2025)
This research discusses the representation of women in four selected songs from Paris Paloma: Labour, Drywall, As Good a Reason, and Last Woman on Earth. The purpose of this research is to uncover how women's experiences are portrayed through song lyrics and how these representations fit into the gynocritical framework proposed by Elaine Showalter. This research uses a qualitative descriptive method, treating song lyrics as literary texts that express emotional burdens, bodily oppression, and women's powerlessness in the face of patriarchal structures. The research emphasizes that contemporary music, particularly lyrics written by female songwriters, serves as a meaningful medium to explore feminist literary expression. The data were analyzed by categorizing the lyrical elements into three aspects: emotional, bodily, and empowerment, based on gynocritical theory. Each lyric represents women not only as victims of societal norms, but also as agents who reclaim their voice and identity. The results show that the songs reflect different stages of women's consciousness, ranging from survival, resistance, and finally autonomy.